Risk Factors for Depression in Children and Adolescents with High Functioning Autism Spectrum Disorders - Myriam De-la-Iglesia; José-Sixto Olivar (The Scientific World Journal)
The objective of our study was to examine, discuss, and provide proposals on diagnostic comorbidity of depression in children and adolescents with high functioning autism spectrum disorder (HFASD) in the following aspects. (1) Prevalence. It was concluded that there are an elevated depression rate and the need for longitudinal studies to determine prevalence and incidence based on functioning level, autistic symptoms, gender, age, type of depression, prognosis, duration, and treatment. (2) Explicative Hypotheses and Vulnerability. The factors that present the greatest specific risk are higher cognitive functioning, self-awareness of deficit, capacity for introspection, stressful life events, adolescence, quality of social relationships, and alexithymia. (3) Risk of Suicide. The need for control and detection of suicidal tendencies and bullying is emphasised. (4) Depressive Symptoms. Indicators for early detection are proposed and their overlap with HFASD is analysed, examining the assessment techniques used and arguing that specific adapted tests are needed.